Rhythm and music for promoting sensorimotor organization in autism: broader implications for outcomes - LaGasse, Blythe; Yoo, Ga Eul; Hardy, Michelle Welde (Frontiers in Integrative Neuroscience, 2024)
Emerging research suggests that music and rhythm-based interventions offer promising avenues for facilitating functional outcomes for autistic individuals. Evidence suggests that many individuals with ASD have music processing and production abilities similar to those of neurotypical peers. These individual strengths in music processing and production may be used within music therapy with a competence-based treatment approach. We provide an updated perspective of how music and rhythm-based interventions promote sensory and motor regulation, and how rhythm and music may then impact motor, social, and communicative skills. We discuss how music can engage and motivate individuals, and can be used intentionally to promote skill acquisition through both structured and flexible therapeutic applications. Overall, we illustrate the potential of music and rhythm as valuable tools in addressing skill development in individuals on the autism spectrum.